Parallel Processing in Visual Search Asymmetry. - Dosher, Barbara Anne; Han, Songmei; Lu, Zhong-Lin (Journal of Experimental Psychology. Human Perception & Performance, 2004)
The difficulty of visual search may depend on assignment of the same visual elements as targets and distractors—search asymmetry. Easy C-in-O searches and difficult O-in-C searches are often associated with parallel and serial search, respectively. Here, the time course of visual search was measured for both tasks with speed-accuracy methods. The time courses of the 2 tasks were similar and independent of display size. New probabilistic parallel and serial search models and sophisticated-guessing variants made predictions about time course and accuracy of visual search. The probabilistic parallel model provided an excellent account of the data, but the serial model did not. Asymptotic search accuracies and display size effects were consistent with a signal-detection analysis, with lower variance encoding of Cs than Os. In the absence of eye movements, asymmetric visual search, long considered an example of serial deployment of covert attention, is qualitatively and quantitatively consistent with parallel search processes. Reprinted by permission of the publisher.